Academic Flow in Higher Education: The Contribution of Self-Compassion and Study Habits - Yusran, Naufal; Wangid, Muhammad Nur; Sabtana, Fayruziyah Ifroch; Ramadhan, Angela Putri (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
Academic flow is an optimal psychological state characterized by intense concentration, intrinsic motivation, and deep engagement in learning activities, which is essential for meaningful learning in higher education. However, many university students experience difficulties in maintaining sustained engagement amid increasing academic demands. This study aimed to examine the influence of self-compassion and study habits on academic flow among fifth-semester undergraduate students at the Faculty of Education, Universitas Negeri Yogyakarta. A quantitative correlational design was employed with a sample of 323 students selected through proportionate random sampling. Data were collected using validated scales of self-compassion, study habits, and academic flow, and analyzed through multiple and simple linear regression techniques. The findings revealed that self-compassion and study habits simultaneously have a significant influence on academic flow, explaining 12.5% of its variance. Partially, self-compassion explains 6.3%, while study habits explain 8.2% of the variance in academic flow. These findings demonstrate that academic flow is shaped by both internal psychological resources and structured learning behaviors. The study provides empirical evidence for integrating emotional resilience development and adaptive study strategies in instructional practices to enhance student engagement and optimize learning outcomes in higher education.